Experimental and analytical analysis on the stacking sequence of composite pressure vessels. (1st September 2020) - Nebe, M.; Asijee, T.J.; Braun, C.; van Campen, J.M.J.F.; Walther, F.
Abstract: The industrialization of fuel cell electric vehicles demands cost efficient storage solutions for hydrogen. While gaseous storage in type IV pressure vessels is currently the most mature technology, further structure optimization needs to be undertaken in order to meet cost requirements. This research investigates the effects of stacking sequence of composite pressure vessels regarding laminate quality, structural deformation and finally burst pressure. Therefore, a known laminate is studied on a subscale vessel geometry with changing stacking sequences. The specimens are pressurized in a specially designed chamber up to burst pressures of 166.11 MPa. Through a multisensor arrangement of stereometric systems, the deformation is tracked up to burst by using 3D digital image correlation. The experimental results show a difference of 67% in burst pressure between the investigated stacking sequences. Experimental cylinder strains and burst pressures are compared to results derived from 3D elasticity theory with implemented first ply failure criterion. Additionally, using X-ray computed tomography and acid digestion tests, insights about the distribution of fiber volume fraction and porosity are provided. For the investigated sequences in this research, the results show the considerable influence of stacking sequence on the laminate quality, the structural deformation and finally the burst pressure of composite pressure vessels. Moreover, it is shown that while the used 3D elasticity approach proved to be a useful tool for the prediction of strains and failure in the cylindrical section, discrepancies between prediction and experiment can arise based on preliminary failure occuring at the cylinder-dome transition. The results therefore emphasize the need for analytical and numerical analysis strategies to consider transition-related effects between cylinder and dome.